When You're Not OK : A toolkit for tough times - Stark, Jill (Brunswick, Victoria : Scribe Publications, 2019)
-- Happy Never AfterThis is a self-care manual for the days when you feel alone -- the days when you worry that you're too weird or broken or unfixable to be normal. With compassion, humour, and honesty, Jill offers signposts to help you findthe path back to yourself. Whether you're having a bad day, or a run of bad days that seems never-ending, When You're Not OK is an emotional first-aid kit for your body, mind, and soul, written by someone who's been there too.
You complete youA table for one; Banish guilt; Ditch the pain olympics; Know your limits; Self-care has no price tag; Remember ... ; 10. Be Kind to Yourself (and Others); The inner critic; Compassion heals; Think the best of people; Do something nice; Anger burns; Try a little tenderness; Music to feed the soul; Play like you're a kid; Ditch perfect; One step forward ... ; Remember ... ; Resources; Acknowledgements
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Online resource; title from digital title page (viewed on May 27, 2020).
Added to collection customer.56279.3
Keywords: Self-actualization (Psychology); Resilience (Personality trait); Electronic books; Self-help publications